2016
DOI: 10.21577/0103-5053.20160220
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Micellar Precipitation for Simultaneous Preconcentration of Benzimidazole Anthelmintics in Milk Samples by High-Performance Liquid Chromatography

Abstract: A method using micellar precipitation process using cationic surfactant cetyltrimethyl ammonium bromide at ambient temperature was investigated for simultaneous determination of benzimidazoles coupled with high-performance liquid chromatography (HPLC) analysis. The studied benzimidazoles was selected as model compounds including thiabendazole, albendazole, mebendazole, and fenbendazole. The experimental parameters affected the extraction efficiency, including the kind and concentration of salt, pH, concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Several different animal tissues were used as samples, and results revealed that this improved method could be a great choice for the determination of benzimidazoles in tissue samples. A few years later, the same group of authors [171] improved the extraction using surfactants in the sample preparation. The proposed extraction technique was performed at room temperature with cationic surfactant cetyltrimethyl ammonium bromide in the absence of dispersive solvent.…”
Section: High Performance Liquid Chromatographymentioning
confidence: 99%
“…Several different animal tissues were used as samples, and results revealed that this improved method could be a great choice for the determination of benzimidazoles in tissue samples. A few years later, the same group of authors [171] improved the extraction using surfactants in the sample preparation. The proposed extraction technique was performed at room temperature with cationic surfactant cetyltrimethyl ammonium bromide in the absence of dispersive solvent.…”
Section: High Performance Liquid Chromatographymentioning
confidence: 99%